2020
DOI: 10.1016/j.jgo.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus nab-paclitaxel followed by maintenance treatment with gemcitabine alone as first-line treatment for older adults with locally advanced or metastatic pancreatic cancer

Abstract: The aim of this study was to evaluate the efficacy and safety of the combination Gemcitabine (Gem) plus nab-Paclitaxel (NabP) (Gem/NabP), followed by maintenance Gem in older adults with locally advanced or metastatic pancreatic cancer (PC). Materials and methods: In this prospective observational study, the induction chemotherapy consisted of NabP 125 mg/m 2 followed by Gem 1000 mg/m 2 on days 1, 8, and 15 of a 4-week cycle. After a maximum of 3 cycles, patients without evidence of progressive disease (PD) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…From May 2015 to June 2019, a total of 317 patients with mPC were recruited across 20 Austrian sites and assigned to first-line treatment with nab-paclitaxel/ gemcitabine. Eighteen patients were excluded owing to no metastasis (12), prior chemotherapy in the metastatic setting (4) or no therapy (2). Hence, 299 patients were eligible for analysis, thus forming the ITT population.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…From May 2015 to June 2019, a total of 317 patients with mPC were recruited across 20 Austrian sites and assigned to first-line treatment with nab-paclitaxel/ gemcitabine. Eighteen patients were excluded owing to no metastasis (12), prior chemotherapy in the metastatic setting (4) or no therapy (2). Hence, 299 patients were eligible for analysis, thus forming the ITT population.…”
Section: Participantsmentioning
confidence: 99%
“…A number of studies examined nab-paclitaxel/ gemcitabine efficacy for elderly patients with mPC, either using the MPACT schedule [9e14] or dose-modified regimens [15e17]. However, except for a few prospective trials [12,17,18], most available data originate from retrospective analyses in diverse, small cohorts of patients with PC [9e11, 13,15,19]. None of them reported prospective, non-interventional evidence with first-line nabpaclitaxel/gemcitabine from a comparably large cohort of elderly patients with mPC.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this strategy has been underevaluated in aPC but is used in other cancers such as colon [10], lung [11], and head and neck cancers [12], making it possible to maintain antitumoral pressure while reducing toxicities [9]. A few studies have addressed the maintenance in aPC: Reni et al [13] sought to show the benefit of maintenance with sunitinib after chemotherapy, whereas Petrioli et al [14] demonstrated that maintenance with gemcitabine after doublet chemotherapy with gemcitabine and nab‐paclitaxel was feasible in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine maintenance after GA was studied for elderly patients in a prospective observational study [41]. A total of 36 patients >70 years with metastatic or locally advanced PDAC initially received GA for a maximum of three cycles (three months).…”
Section: Maintenance Therapymentioning
confidence: 99%